Bank financing and economic stability : an oxymoron? - Theodore, Karl (UWI St. AugustineTT, 2009)
Focuses on the proven vulnerability of the real sector of the economy to convulsions in the financial sector. Considers whether there is a role that non-bank socially oriented institutions can play in providing for the financing of the business sector of the economy.